Staphylococcus aureus: Resistance patterns to antimicrobials and Penicillinase among strains isolated from apparently healthy lactating cows - deAraujo, MLC; Andrioli, J. L. (Soc Brasileira Microbiologia, 1996)
Ninety-two strains of Staphylococcus aureus isolated from the nasal fossa and udder skin of apparently healthy lactating cows were analyzed for resistance to antibiotics and production of penicillinase.The results showed a greater frequency of resistance patterns to penicillin and ampicillin.All strains were sensitive to oxacyllin and gentamicin.The most frequent Barber and Burston model was SSSS (60.90%), followed by RSSS (18.50%).With respect to the production of penicillinase although the Lucas method indicated a larger number of positive samples, we suggest the use of the Haight and Finland method due to a greater consistency of data obtained with it.
Keywords: Staphylococcus aureus; antibiogram; penicillinase